For a less dramatic creative destruction: Innovation and entrepreneurship as features of the market process - D’Andrea, Fernando; Mazzoni, João Fernando (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
Innovation is at the core of any market economy and it is necessary for any organization to survive in competitive environments. This article aims to discuss the current approach to innovation seen in most of the management and economics literature and it will suggest that this understanding, loosely based on Schumpeter’s ideas on creative destruction, is not capable of representing the actual dynamism seen in the markets. In order to better understand that dynamism, the market process approach of the Austrian School is presented as a substitute. The comparison indicates that adopting the market process approach, in which entrepreneurship and innovation are endogenous and not-necessarily related to breaks or shocks, leads to a much better understanding of the innovation phenomena and, consequently, and opens new paths in the understanding of the entrepreneurial role. The work concludes presenting limitations and suggestions for future research in management, and economics, and finally, some pedagogical suggestions are also given.